2022
DOI: 10.2991/ahsr.k.220108.023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Safety Building Facilities as a Fire Prevention Effort at the State University of Malang’s Faculty of Sports Science

Abstract: A fire hazard is one of the potential hazards of Occupational Safety and Health or K3 in buildings. In high-rise buildings, escape routes are few and limited, necessitating the implementation of effective, efficient, and integrated fire prevention measures. The purpose of this study is to determine the completeness of safety building facilities, to identify and analyze the feasibility of safety building facility function, and to design efforts to optimize the functional safety building facilities in the C6 FIK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Therefore, the building was required to be protected safely from fire [10]. Several studies on fire protection of laboratory buildings have suggested that re-arranging the sprinkler distance and fire extinguishers [8], forming a fire emergency response team [11], periodically inspecting and replacing fire safety [12], and improving student knowledge of fire safety [13] are among the solution implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the building was required to be protected safely from fire [10]. Several studies on fire protection of laboratory buildings have suggested that re-arranging the sprinkler distance and fire extinguishers [8], forming a fire emergency response team [11], periodically inspecting and replacing fire safety [12], and improving student knowledge of fire safety [13] are among the solution implemented.…”
Section: Introductionmentioning
confidence: 99%